Enhancing Service Brand Passion Through Self-Congruity: The Moderating Role of Gender and Age - Gilal Faheem Gul; Memon Amjad Ali; Gilal Naeem Gul; Gilal Rukhsana Gul; Memon Ahsan Ali (Central European Management Journal, 2022)
Purpose: Using congruity theory, triangular theory of love, gender schema theory, and generational cohort theory, this study aimed to examine the relationships between congruity types and consumers’ service brand passion, along with the moderation effect of gender (i.e. male vs. female customers) and age (i.e. young vs. older customers) in these relationships.